Growth of defect-free GaAsSbN axial nanowires via self-catalyzed molecular beam epitaxy. (26th October 2017) - Sharma, Manish; Deshmukh, Prithviraj; Kasanaboina, Pavan; Reynolds, C Lewis; Liu, Yang; Iyer, Shanthi
Abstract: Bandgap reduction of 10% by incorporation of a dilute amount of N is reported for the first time, in axial GaAsSb nanowires (NWs) grown on Si (111) via Ga-assisted molecular beam epitaxy. Impact of N incorporation on the surface morphology, NW growth kinetics, and their structural and optical properties were examined. Dilute nitride NWs with Sb composition of 7 at% did not exhibit any noticeable planar defects, as revealed by the absence of satellite twin peaks in the selected-area diffraction pattern and high-resolution transmission electron microscopy imaging. Point defects were also minimal in as-grown dilute nitride NWs, as ascertained from the comparison of low-temperature photoluminescence spectra as well as the shape and shift of Raman modes, with in situ annealed NWs in different ambients. Evidence of enhanced incorporation of N was found in the NWs in situ annealed in N ambient, but with deteriorated optical quality due to simultaneous creation of N-induced defects. The lack of any noticeable defects in the as-grown GaAsSbN NWs demonstrates the advantage of the vapor–liquid–solid mechanism responsible for growth of axial configuration over the vapor–solid growth mechanism for core–shell NWs as well as their thin film counterpart, which commonly exhibit N-induced point defects.